A complete demand system of food in Malaysia - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Abdullah, Amin Mahir; Radam, Alias (The Icfai University Press, 2008)
There has been a notable success in the Malaysian economy, with its countrymen getting wealthier and food consumption undergoing transitional changes. This study intends to analyze the complete demand system of food in Malaysia by using the Household Expenditure Survey 2004/2005 via the Linear Approximate Almost Ideal Demand System (LA/AIDS) model. As expected, the estimated own-price elasticities for all foods follow the law of demand. The empirical results show that the demand for all foods in response to the income is relatively positive, with expenditure elasticities of meat (1.110), fruits (1.341), vegetables (1.341), sugar and beverage (1.039) and other foods (1.115) being elastic. This study shows that the Malaysian food consumption pattern is not only moving towards higher value food products (especially meats) but also functional foods (fruits and vegetables) as the per capita income of Malaysians increases.